2014
DOI: 10.1515/ijnes-2013-0019
|View full text |Cite
|
Sign up to set email alerts
|

Development, Implementation and Evaluation of a Peer Review of Teaching (PRoT) Initiative in Nursing Education

Abstract: AbstractFor many years, an area of research in higher education has been emerging around the development and implementation of fair and effective peer evaluation programs. Recently, a new body of knowledge has developed regarding the development and implementation of fair and effective peer evaluation programs resulting in formative and summative evaluations. The purpose of this article is to describe the development, implementation, and evaluation of a peer review of teaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(58 citation statements)
references
References 16 publications
0
58
0
Order By: Relevance
“…9,21,22 While there is some consistency in the actual process of peer assessment, it seems to be common that most programs are developed and tailored to a specific setting. 17,18,22,23 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9,21,22 While there is some consistency in the actual process of peer assessment, it seems to be common that most programs are developed and tailored to a specific setting. 17,18,22,23 …”
mentioning
confidence: 99%
“…Depending on the intention of the process, peer assessment is commonly seen as a threat by teaching faculty members, no matter the discipline. 9,18,19,24,25 Anxiety and stress are noted to be common feelings among teaching faculty, where the process of peer assessment is meant for evaluation purposes and is mandatory, and where those involved are unable to choose a peer to be their assessor.9,18 Peer assessment processes, where the program is voluntary and where faculty members are able to self-select their peer assessor, reported easing of such feelings of threat and anxiety, 17,19,21,22,25 lending to the support of a program that is meant to be developmental rather than evaluative in nature.Common in the literature is the need for some structure to the process. 9,19,26 Peer assessment processes tend to be better received by teaching faculty when there is an element of training involved.…”
mentioning
confidence: 99%
“…6,22 Alternatively, Mager et al described a model where peer review of teaching was both formative and A J P E A c c e p t e d D r a f t summative using a rubric that gave the reviewee several options to choose from for inclusion in the review; this was suggested to increase the faculty member's trust in the process. 10 This study had some limitations which may affect the applicability of the findings. First, as previously mentioned, there are several models of peer review that have been described in the literature many of which involve multiple visits, more comprehensive examination of course materials and consultation between reviewer and reviewee.…”
Section: A J P Ementioning
confidence: 89%
“…5,6 Adoption of peer review pairs (using a reciprocal process with the observer and observee) has been suggested in the literature, as has the use of a cross-disciplinary reviewers that can focus more on pedagogy than content. 2,10 Finally, the School of Pharmacy will clarify whether the review is to be used for formative or summative purposes. Other institutions have suggested that it be used primarily for formative purposes, but individual instructors can opt to include the review in promotion packages.…”
Section: A J P Ementioning
confidence: 99%
See 1 more Smart Citation